Ocular tissue interactions during the development of human fetal neuroretina grafted into nude mice - Angioi, Karine; Hatier, Renée; Duprez, Adrien (Development, growth & differentiation, 2003)
To determine the roles of different ocular tissues in the development of the human fetal neuroretina, a study ethically and technically impossible in human subjects, human embryonic and fetal retinas were heterotopically implanted into nude mice. Ninety‐five eyeballs were obtained from legally aborted 6‐ to 7‐week‐old embryos or 8‐ to 10‐week‐old fetuses. Ten isolated neuroretinas with vitreous but without pigment epithelium, 20 half‐eyeballs and 70 intact eyeballs, of which 12 had a thick layer of periocular tissue, were microsurgically grafted. Five intact eyeballs were used for reference. Over a period of 1–245 days, all of the grafts were removed for light and electron microscopy observations. All of the isolated neuroretinas had disappeared by the second day after transplantation. Grafts of the posterior section of the eyeball contained only some clusters of pigment epithelium, occasionally covered with undifferentiated neuroretinal cells. Grafts of the retrolental section of the eyeball contained small areas of dysplasic neuroretina with folds and rosettes. Grafts of the 70 intact eyeballs were successful, but only 26 showed normal histological organization of the choriocapillaris, the retinal pigment epithelium and the neuroretina in the posterior part of the posterior chamber. Photoreceptor differentiation was evident in these retinas after approximately 80 days of transplantation and was complete after 166 days. Their anterior part was always dysplasic, with occasional ciliary differentiation. Twenty‐three grafted eyeballs had a dysplasic neuroretina with folds, rosettes and necrotized areas. Twenty‐one were atrophic, 12 of which were the eyeballs grafted with periocular tissue. These results demonstrate the role of the fetal mesenchyme and pigment epithelium in the rapid revascularization, and subsequent survival and tissue organization, of the neuroretina. The stratified development of the neuroretina required a thin mesenchymal environment for revascularization of the graft by human vasculogenesis or neoangiogenesis and a normal retinal pigment epithelium for normal neuroretinal differentiation. When these conditions were not satisfied, the neuroretina disappeared or was dysplasic, partly necrotized or atrophic. This model might prove useful for a number of therapeutic or clinical studies.